Protected areas and spatial conservation priorities for endemic vertebrates of the Gran Chaco, one of the most threatened ecoregions of the world - Nori, Javier (2016)
Aim: To evaluate the representativeness of the current network of protected areas (PAs) of one of the most threatened ecoregions in the world, the South American Gran Chaco, and determine priority conservation areas for endemic (and nearly endemic) terrestrial vertebrates of the region. Location: South America. Methods: We identified all those amphibians, mammals and birds whose distributions were at least 70% within the Gran Chaco. Then, we refined and corrected species’ distributional ranges, first, using records from collections and expert knowledge, and second, by incorporating environmental and topographic data using a technique for range polygon refinement. Lastly, we used Zonation, a spatial conservation prioritization software, to evaluate representativeness of the current protected areas (PAs) network of the region and to define forest remnants to strategically expand PAs while maximizing the representativeness of the selected groups and considering human activities. Results: Current PAs cover 9% of the region and represent 9.1% of the total distribution of endemic species. Considering our prioritization, increasing the coverage to 17% to match the Aichi targets would substantially increase the representativeness of the PA network, covering on average more than 30% of the ranges of all endemic species and 77% of the distributions of threatened and DD endemic species. Main conclusions: Our results highlight that the need for well-informed decisions in the Gran Chaco is imperative. While the current PA network in the region ensures a very poor representation of endemic terrestrial vertebrates, opportunities to efficiently expand the PAs network are really high. This emphasizes the potential of complementarity-based systematic conservation planning tools as an essential support for conservation decisions. Given the great information gaps regarding biodiversity and human activities in the region, similar studies with updated data would improve conservation planning in the Gran Chaco in the future.